A form of dysplasia or a fortuitous association? A cerebral aneurysm inside an arachnoid cyst: case report - Zanini, Marco Antonio [UNESP]; Faleiros, Antonio Tadeu de Souza [UNESP]; Rondinelli, Gilberto; Gabarra, Roberto Colichio [UNESP]; Resende, Luiz Antonio de Lima [UNESP] (Lippincott Williams & Wilkins, 2007)
OBJECTIVE: Although arachnoid cysts and intracranial aneurysms are very common lesions, their association in the same patient is rare. We present a case of a middle cerebral artery aneurysm ruptured into an arachnoid cyst. We found only six cases with intracystic hemorrhage reported in the literature. The presence of an arachnoid cyst can mislead clinical presentation. The patient presented a paradoxically small temporal fossa and thickening of the temporal and sphenoid bone. The authors suggest that this uncommon association (arachnoid cyst, atypical cranial vault, and mirror-like cerebral aneurysm) could represent a form of dysplasia. CLINICAL PRESENTATION: A 46-year-old patient presented with a 3-week history of slight headaches, which had worsened in the last 3 days before presentation. Computed tomographic scans showed a cystic lesion located in the middle cranial fossa and sylvian fissure with suspected aneurysm dilation inside. Magnetic resonance imaging scans showed an intracystic hemorrhage but not subarachnoid hemorrhage. Paradoxically, changes in the cranial vault around the cyst were noted. Digital subtraction angiography showed bilateral mirror middle cerebral artery aneurysms. INTERVENTION: A large right pterional craniotomy was performed with full microsurgical removal of the arachnoid cyst walls and aneurysm clipping. The aneurysm was in the medial wall of the arachnoid cyst with its dome inside the cyst. The contralateral aneurysm was clipped 2 weeks later. The follow-up period was uneventful, and the patient returned to normal life. CONCLUSION: Rupture of a cerebral aneurysm into an arachnoid cyst is rare. Clinical presentation may be unusual because the cyst can prevent subarachnoid hemorrhage. A middle fossa cranial arachnoid cyst in the presence of temporal bone depression, small middle fossa, and thickness of squamous temporal bone and the lesser wing of sphenoid is rare and suggests that congenital factors may play an important role in their development. The exceptional association between mirror aneurysms and arachnoid cyst with bone changes suggests a possible congenital form of dysplasia. Copyright © by the Congress of Neurological Surgeons.
Keywords: Arachnoid cyst; Cerebral aneurysm; Cranial vault; Dysplasia; Intracystic hemorrhage